If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3(n + 6) = -9 Reorder the terms: 3(6 + n) = -9 (6 * 3 + n * 3) = -9 (18 + 3n) = -9 Solving 18 + 3n = -9 Solving for variable 'n'. Move all terms containing n to the left, all other terms to the right. Add '-18' to each side of the equation. 18 + -18 + 3n = -9 + -18 Combine like terms: 18 + -18 = 0 0 + 3n = -9 + -18 3n = -9 + -18 Combine like terms: -9 + -18 = -27 3n = -27 Divide each side by '3'. n = -9 Simplifying n = -9
| 4(7x-1)=3(2x-1)-4(x+6) | | (-2/5)3 | | w^2+16w+64=0 | | 5x+6=106 | | X^2=80X | | 4-3p=-2 | | 10v=60 | | 2(3-w)+6=-6(w-2)-7 | | 0(-8/7) | | X^2=34X | | -6/7w=-42 | | 4x^2-24x=-27 | | -8/15-23/25 | | 1/3(3x-9)=-10+6+3(2-x) | | 6(2x+1)=10x+4 | | 12x-10=10x-6 | | 0=4(-4x^2+10x-6) | | 3(x+14)=69 | | z^2+6z-27=0 | | -36=4v+4(v+7) | | 5/6*2/3=x | | -19/35+4/15 | | 3x^2+5=65 | | 9=3x-7 | | -120x+3000=-160x+4000 | | 7+2x=5x-5 | | 4x+2=32 | | 67-3x=9x+16 | | 7/9y+2+5/9y+6 | | 3a+2a=135 | | x-.3x=105 | | 4+8r-3=7r+29-3r |